REKONSTRUKSI FILSAFAT ILMU DALAM PRAKTIK PENGELOLAAN PENDIDIKAN ISLAM: SEBUAH KAJIAN KONSEPTUAL - Ghofur, Mahmud Abdul; Purwantara, Rizky Aji; Rofiq, Ainur (Hijri, 2025)
The purpose of this study is to formulate a conceptual framework for reconstructing the philosophy of science as a reflective foundation in the practice of Islamic education management, so that managerial strategies and policies in educational institutions are not only technically effective but also aligned with the scientific principles and normative values of Islamic education. This research employs a library research approach to formulate a conceptual framework for reconstructing the philosophy of science as a reflective foundation in the management of Islamic education. Data are collected from academic books, journals, policy documents, and institutional reports, then analysed thematically to identify the relationship between the ontological, epistemological, and axiological dimensions of the philosophy of science and managerial practices, policies, and supervisory mechanisms. The results are expected to produce an applicable and normative conceptual framework that strengthens governance, quality assurance, and the alignment of scientific values in Islamic education in a holistic and transformative manner. The findings of this study show that the integration of the philosophy of science into the management of Islamic education plays a strategic role as a reflective foundation that enhances managerial quality and the achievement of educational goals. This approach enables managers to align policies and operational practices with ontological, epistemological, and axiological principles, so that decisions are not merely technocratic but are oriented toward the moral, intellectual, and spiritual transformation of learners. A strong philosophical foundation bridges the gap between practice and scientific values, improves governance and quality assurance, and strengthens evaluation and supervision mechanisms that are holistic, accountable, and sustainable. Thus, Islamic education management based on the philosophy of science enables transformative, holistic managerial practices that are consistent with scientific values